A case report of early diagnosis of asymptomatic hairy cell leukemia using flow cytometry - Tadros, James; Davis, Amanda; Awoleye, Oreoluwa; Vassiliou, Evros (Frontiers in Immunology, 2023)
Hairy Cell Leukemia is an infrequent leukemia that can be recognized both microscopically and flow cytometrically once the patient develops symptoms. We present a case where early diagnosis was achieved using flow cytometry long before the patient became symptomatic. This was achieved by focusing on a small percentage (0.9%) of total leukocytes that exhibited a higher side scatter and brighter CD19/CD20 than the remaining lymphocytes. A bone marrow aspirate three weeks later confirmed the presence of malignant B-cells. Shortly after, the patient presented splenomegaly and complained of fatigue.